Perlindungan Hukum bagi Notaris melalui Peningkatan Peran Majelis Pengawas Notaris dalam Mencegah Pelanggaran Kode Etik di Kota Kupang - Vany Kurniaty Plaituka; Yossie M. Y Jacob; Rini Marselin Kaesmetan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study examines legal protection for notaries through strengthening the role of the Regional Supervisory Council in preventing violations of the notarial code of ethics in Kupang City. The research employed an empirical legal method with a descriptive qualitative approach. Primary data were collected through interviews with seven respondents consisting of representatives of the Regional Office of the Ministry of Law of East Nusa Tenggara, members of the Regional Supervisory Council, and practicing notaries, while secondary data were obtained from legislation, official documents, books, and scientific literature. The findings indicate that legal protection for notaries is implemented through preventive and repressive mechanisms. Preventive protection includes the authority to refuse unlawful deeds, the right of refusal, and the obligation to maintain professional confidentiality, whereas repressive protection is provided through professional legal assistance, approval from the Notary Honorary Council before legal summons, and the right to defense during ethical proceedings. The Regional Supervisory Council contributes to preventing ethical violations through supervision, guidance, protocol examination, mediation, complaint handling, and ethical education. However, the effectiveness of these functions requires stronger institutional capacity, improved inter-agency coordination, and continuous professional development to ensure legal certainty, uphold professional integrity, and enhance public trust in notarial services.